ENGLISH SPEAKING PRACTICE IN PUBLIC PLACES: IS IT SOCIALLY ACCEPTABLE OR AN ACT OF COCKINESS? - Ridhwan Moehamad (Politeknik Negeri Sriwijaya, 2014)
As Indonesian people whose mother tongue is not English, we seldom use this foreign language for our daily communication. Its usage is confined within the walls of our classrooms in which this language may find its way to be recognized by the students. Under those circumstances, it is not surprising that English is rarely spoken on our streets or in any other public places. This kind of attitude, daring to use a foreign language in a place where all the other people do not use them, is sometimes met with unsympathetic glances or unfriendly stares. This may cause those energetic learners of English to think twice to use this language orally in public places. They are afraid of being mocked, ridiculed, or even considered snobs. This condition will lead to their losing courage to apply the theoritical English they have learned in their classes to the real contexts that may include those public places. This paper is, therefore, made to include a small research to investigate if this kind of discomfort and fear is unfounded. The research proves that most people do not object to hearing English spoken by other people of their own race or nationality on their streets or public places as long as these speakers can keep to normal level of loudness and appropriateness of speech and behavior.